Cooperative Training, Self Efficacy And Organizational Commitments Of Cirebon Save And Loan Cooperatives (KSP) During A Pendemi - Anna Suzana; Yodi Rudiantono (Journal of Bussines Management Basic, 2022)
This study aims to identify and analyze cooperative training, self-efficacy and organizational commitment of the Cirebon savings and loan cooperatives (KSP) during the pandemic from a total of 21 Cirebon city cooperatives, with the same average difficulty and needs, especially, having the aim of providing services and accommodating the needs of members based on AD/ART agreement. A total of 63 cooperative administrators consist of the chairman, secretary and treasurer. The technique for measuring the number of samples uses the Slovin formula with a margin of error of 10%. Explanatory survey method (explanatory survey) method of explanatory survey, the hypothesis is tested by means based on observations of the consequences that occur and look for the causal factors through certain data. The samples taken in this study were 63 respondents. The method in collecting this data uses a questionnaire, while the method in this study uses multiple linear regression analysis. The results of this study indicate that Cooperative Training has a positive and significant effect on Cooperative Organizational Commitment as seen from tcount > t table ie 6.512 > 1.670, Self Efficacy has a positive and significant effect on Cooperative Organizational Commitment seen also from tcount > t table that is 9.588 > 1.670 and simultaneously variable Training Cooperatives and self-efficacy have a positive and significant effect on Cooperative Organizational Commitment, as shown by Fcount>Ftable, namely 57,183>3,15. From all the results, both partially and simultaneously have a sig value less than 0.05 or 0.000 <0.05.